Public Debt, Current Account Balance, and Fiscal Balance: The Threshold Effects in Selected ASEAN Countries - Soo, Xin-Lin; Kueh, Jerome Swee-Hui; Ab-Rahim, Rossazana; Yau, Josephine Tan-Hwang (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Indebtedness is a huge global issue faced by all economies around the world since the older time until today. The high and increasing debt levels have become a concern, and public debt has become the core of the turmoil that began a few years ago. When the government’s spending in a year exceeds its revenue, there will be a budget deficit for that fiscal year. Hence, it must use debt to fill the funding gap. This situation creates an annual deficit, which cannot end until the accumulated debt becomes unsustainable and the government’s finances collapse. Hence, this study is aimed to assess the impact of the public debt threshold on current account balance and fiscal balance in selected ASEAN countries (Indonesia, Malaysia, Philippines, Singapore, Thailand, and Vietnam) by adopting annual data from 1990 to 2021. In panel long run estimation by pooled mean group (PMG) estimator, public debt affects twin balances to have a positive relationship. In the empirical analysis, the single threshold sample splitting model is employed to assess the impact of the public debt threshold on the current account balance and fiscal balance either below or above the threshold level. The outcomes indicate that the public debt threshold level is at 63.36%. When the public debt threshold is below 63.36%, there is a negative relationship between the current account balance and fiscal balance; whereas when the public debt threshold is higher than 63.36%, there is positive nexus between the current account balance and fiscal balance. This result implies the situation of twin divergence situation when exceeding the public debt threshold level.